Digital Meets Distribution: Quantifying the Impact of Logistics Integration in Emerging Market Omnichannel Retail - Akbariani, Nurhaliza Vania; Setiyowati, Harlis (Indonesian Scientific Publication, 2024)
This study examines the impact of omnichannel logistics integration on retail service level performance in Indonesia between 2020 and 2024. Amidst rapid digital transformation in Southeast Asia, major Indonesian retailers such as AMRT, MIDI, MAPI, and LPPF have implemented innovations including store hubs, click-and-collect, and Pay & Pick services to meet evolving consumer expectations. Using firm-level quarterly panel data and employing fixed effects and event study models, the study analyzes how omnichannel logistics adoption represented by infrastructure investments and digital feature rollout affects service-level indicators such as inventory turnover, fill rate, and on-time delivery. The findings indicate that logistics integration significantly improves service metrics, with firms observing a 4–6% improvement in performance indicators within two quarters of implementation. This underscores the strategic value of aligning digital and physical infrastructure in emerging markets, offering evidence that logistics integration enhances both operational efficiency and service quality. The study contributes to both theoretical literature and practical retail strategies by framing omnichannel performance through a quantitative, data-driven lens.